Experimental Setup to Validate the Effects of Major Environmental Parameters on the Performance of FSO Communication Link in Qatar - Amith Khandakar (14151981) (2018)
Weather conditions and chemical composition of the atmosphere are the most uncontrollable challenges for free-space optical (FSO) communications. Environmental parameters contribute directly in the characterization of atmospheric turbulence. Thus, it is very interesting to prepare a test setup to study the effect of such parameters on FSO transmissions especially in a region like Qatar, which is arid and has harsh climate. Unlike that of Europe and USA, Qatar’s climate is characterized by high temperatures throughout the year, exceeding 14 °C even in winter. The experiment was carried at Qatar University (QU) using a system that comprises of two Field Programmable Gate Array (FPGA) boards and two FSO terminals installed at 600 m apart from each other. Each terminal operates at 1550 nm and had a capacity of 1 Gb/s. On the other hand, the environment parameters were recorded using a weather station installed near the transmitter. To have a wider set of data for analysis, parameters from four different seasons were recorded and analyzed. We present a comparison between the FSO performances for the different seasons in terms of Packet Delivery Ratio (PDR). We notice a significant difference in the behavior of FSO during summer and winter seasons. Furthermore, using statistics on the data collected from the weather station and based on Blaunstein model (BKB), we correlate the FSO behavior to the variation of refractive index (Cn2) in winter. Also a closed form expression, estimated from the statistical data, has been derived to relate the PDR with environmental parameters for the summer season. Other Information Published in: Applied Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/app8122599